TRANSLATION STRATEGIES USED IN THE SUBTITLE OF PERUNDUNGAN FROM INDONESIA INTO ENGLISH - Hayon, Emanuel B; Jedho, Fransiska; Zoba, Yohana; Kobun, Maria Y K; Zaun, Bernadeta M; Sama, Gratiana (Lantern: Journal of Language and Literature, 2025)
This article analyses the translation strategies of the film text in the second part of the film “PERUNDUNGAN” entitled “Jamuan Terakhir”. The research aims at identifying gaps in translation that may affect the audience's understanding of the emotional and narrative context of the film. Using a descriptive qualitative method, data were collected from dialogue transcripts and film texts, which were then analyzed based on Gottlieb's theory of eleven translation strategies. The results showed that transfer translation strategy dominates with 51 data (79.69%), followed by paraphrase with 8 data (12.5%), and the rest use Imitation with 1 datum (1.56%), addition 1 datum (1.56%), Condensation 1 datum (1.56%) while Taming 2 data (3.12%). The findings highlight that the use of inappropriate strategies can reduce dramatic intensity and disguise important messages, especially in the context of sensitive themes such as sexual violence and psychological trauma. Therefore, this study recommends the application of more appropriate strategies to improve the quality of audiovisual translation, especially in subtitles that relate to the context of bullying.